Producción orgánica de fresa (Fragaria spp.), Las Sabanas Madriz, Nicaragua. - Benavidez Gonzales, -lvaro Nicolás; Cisne Contreras, José Dolores; Moran Centeno, Juan Carlos; Duarte Canales, Henry Alberto (Managua (Nicaragua), 2022)
(Es)
Ilus.; 22 ref.,; Existe en formato impreso y electrónico.
Keywords: MADRIZ; FITOSANITARIO